Nature and Degree of Severity of Consultations in Gynecological Emergencies: A Tunisian prospective study - Aloui, Haithem; Azouz, Eya; Hatem, Frikha; Rami, Hammami; Hassine, Abouda Saber; Badis, Chanoufi (Indonesian Socety of Obstetrics and Gynecology, 2025)
AbstractIntroduction: Gynecological emergencies are often crowded with false emergencies. They overwhelm doctors who also have to manage the birth room. The main objective of our work was to assess the type and degree of severity of pathologies encountered in gynecological emergencies.Methods: This is a prospective descriptive study, carried out in the gynecological emergencies of the Mongi Slim hospital, Tunisia, from July 1 to July 21, 2023. We have defined the reality of the emergency as the main endpoint and we have classified the women in three groups: